Electron Microscopy Novel Microscopy Trends - Arita, Masashi; Sakaguchi, Norihito (IntechOpen, 2019)
TEM and SEM have contributed greatly to the progress of various research fields, which has been accelerated in the last few decades by highly functional electron microscopes and microscopy. In this tide of microscopy, various microscopic methods have been developed to make clear many unsolved problems, e.g. pulse beam TEM, environmental microscopy, correlative microscopy, etc. In this book, a number of reviews have been collected concerning these subjects. We think that the content in each chapter is impressive, and we hope this book will contribute to future advances in electron microscopy, materials science, and biomedicine.